2015
DOI: 10.1152/ajpcell.00227.2014
|View full text |Cite
|
Sign up to set email alerts
|

Loss of mitochondrial exo/endonuclease EXOG affects mitochondrial respiration and induces ROS-mediated cardiomyocyte hypertrophy

Abstract: Tigchelaar W, Yu H, de Jong AM, van Gilst WH, van der Harst P, Westenbrink BD, de Boer RA, Silljé HH. Loss of mitochondrial exo/endonuclease EXOG affects mitochondrial respiration and induces ROS-mediated cardiomyocyte hypertrophy. Am J Physiol Cell Physiol 308: C155-C163, 2015. First published November 5, 2014 doi:10.1152/ajpcell.00227.2014.-Recently, a locus at the mitochondrial exo/endonuclease EXOG gene, which has been implicated in mitochondrial DNA repair, was associated with cardiac function. The funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Conversely, depletion of nucleases that are critical for nuclear BER, flap endonuclease 1 (FEN1) and DNA2 has no or limited effect on mtDNA14. Ectopic expression of hEXOG increases resistance to oxidative stress of proliferating myoblasts15, and depletion of EXOG increases oxidative consumption rate in primary neonatal rat ventricular cardiomyocytes16. These studies provide strong support to the idea that hEXOG is involved in mtDNA repair.…”
mentioning
confidence: 63%
“…Conversely, depletion of nucleases that are critical for nuclear BER, flap endonuclease 1 (FEN1) and DNA2 has no or limited effect on mtDNA14. Ectopic expression of hEXOG increases resistance to oxidative stress of proliferating myoblasts15, and depletion of EXOG increases oxidative consumption rate in primary neonatal rat ventricular cardiomyocytes16. These studies provide strong support to the idea that hEXOG is involved in mtDNA repair.…”
mentioning
confidence: 63%
“…The decline in maximal respiration and reserve capacity was the first sign that mitochondrial respiration was hampered in EXOG-depleted cells stimulated with PE, which ultimately resulted in cell death. As EXOG depletion-induced ROS production could not be decreased by treatment with MitoTEMPO, we suggest that increased ROS levels are implicated in several other effects on the cell, including cardiac hypertrophy [14]. In endothelial cells, the exhaustion of the reserve capacity by ROS leads to mitochondrial protein modifications, ultimately resulting in cell death [27,28].…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, the EXOG-containing locus was previously identified in a genome-wide association study on QRS duration, which is a risk factor for heart failure [15]. These increased ROS levels triggered cell growth, resulting in a hypertrophic phenotype [14]. We reported that in EXOG-depleted cardiomyocytes, mitochondrial respiration is strongly enhanced and a concomitant increase in ROS has been observed.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations